UPAYA PENCEGAHAN DAN PENGENDALIAN COVID-19 MELALUI PEMBUATAN DAN PENDISTRIBUSIAN ALAT PELINDUNG DIRI PADA BERBAGAI PUSKESMAS DI KOTA PADANG - Efrida Efrida; Fachzi Fitri; Sukri Rahman; Ade Asyari; Al Hafiz; Dolly Irfandy; Yan Edward; Novialdi Novialdi; Bestari Jaka Budiman; Effy Huriyati; Jacky Munilson; Nirza Warto; Rossy Rosalinda (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
The Covid-19 case that has spread in Indonesia requires efforts from various parties to resolve it. The Faculty of Medicine, Andalas University, is also making efforts to prevent and control Covid-19. The purpose of this activity is to minimize the possibility of the rapid spread of Covid-19 and preventive efforts to keep the people around Pauh, Kuranji, and Air Cold healthy and protected from Covid-19. This activity was carried out in three health centers: Pauh Puskesmas, Kuranji Health Center, and Padang City Puskesmas Air Cold. The method used is KIE (Educational Information Communication) about the COVID-19 disease in publishing articles in the mass media and giving masks. The target of the activity is the community around Pauh, Kuranji, and Air Cold Padang City. The results of the activities obtained include producing PPE (Personal Protective Equipment) as many as 80 face shields, 400 masks, and 60 hazmat suits involving MSMEs (Micro, Small, and Medium Enterprises) and convection. Furthermore, this PPE is distributed to health centers in need, namely Pauh Puskesmas, Kuranji Health Center, and Puskesmas Air Cold Padang City. Furthermore, it is distributed to parties in need, namely the public and medical personnel. The Covid-19 prevention and control program is carried out to suppress and reduce the positive number of Covid-19 and protect medical personnel from providing top service to patients. Furthermore, making PPE that involves MSMEs and convection can help the community's economy, which has declined due to this pandemic.